2020
DOI: 10.1634/theoncologist.2019-0766
|View full text |Cite
|
Sign up to set email alerts
|

Novel Models Predict Postsurgical Recurrence and Overall Survival for Patients with Hepatitis B Virus-Related Solitary Hepatocellular Carcinoma ≤10 cm and Without Portal Venous Tumor Thrombus

Abstract: Background. The predictive model of postsurgical recurrence for solitary early hepatocellular carcinoma (SE-HCC) is not well established. The aim of this study was to develop a novel model for prediction of postsurgical recurrence and survival for patients with hepatitis B virus (HBV)-related SE-HCC ≤10 cm. Patients and Methods. Data from 1,081 patients with HBVrelated SE-HCC ≤10 cm who underwent curative liver resection from 2003 to 2016 in our center were collected retrospectively and randomly divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…(ALBI grade) and systemic inflammatory and immune factors (NLR), thereby yielding higher C-indexes, which was consistent with one recently reported study [31].…”
Section: Discussionsupporting
confidence: 93%
“…(ALBI grade) and systemic inflammatory and immune factors (NLR), thereby yielding higher C-indexes, which was consistent with one recently reported study [31].…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Table S6, the univariable Cox regression analysis indicated that BCLC stage, AJCC stage and tumor size were associated with overall survival (OS) and recurrence free survival (RFS) of HCC patients receiving radical treatment, which is greatly consistent with previous reports (23). Furthermore, HCC patients were respectively strati ed by cut-off value of three genome-wide CNV indicators determined by maximizing Youden index.…”
Section: Concordant Pro Le Of Cnvs Was Observed Between Cfdna and Tumsupporting
confidence: 84%
“…Overall, 5083 patients from the 11 retrospective cohort studies were included in this study (12)(13)(14)(15)(17)(18)(19)(20)(21)(22)(23). The level of evidence was 2a.…”
Section: Characteristics Of the Selected Articlesmentioning
confidence: 99%